A Highly Flexible and Lightweight MnO2/Graphene Membrane for Superior Zinc‐Ion Batteries - Wang, Jinjin; Wang, Jian‐Gan; Liu, Huanyan; You, Zongyuan; Li, Zhen; Kang, Feiyu; Wei, Bingqing (Advanced functional materials, 2021)
Batteries powering next‐generation flexible and wearable electronic devices require superior mechanical bendability and foldability. Herein, a self‐standing hybrid nanoarchitecture constructed by ultralong MnO2 nanowires and graphene nanosheets as an advanced and lightweight cathodes for flexible and foldable zinc‐ion batteries (ZIBs) is designed and fabricated. The new‐designed batteries exhibit not only a high energy density of 436 Wh kg−1 based on the total cathode mass but also good 2000‐cycling durability. More importantly, the shape‐deformable ZIBs can be operated without any capacity loss under both bent and folded circumstances. The foldable ZIBs with high energy density and long lifetime hold great promise for smart and wearable electronics. A freestanding MnO2/graphene hybrid membrane is fabricated to construct highly flexible and foldable zinc‐ion batteries that delivers an unprecedented high energy density of 436 Wh kg−1 based on the total cathode mass and long lifetime over 2000 cycles.